Uji Aktivitas Antidiare Madu dan Kombinasi Madu dengan Infusa Daun Jambu Biji (Psidium guajava L.) terhadap Mencit - Rany Silvi Mova Kalanarky; Fajar Prasetya; Nurul Annisa (Proceeding of Mulawarman Pharmaceuticals Conferences, 2020)
Diarrhea is a major cause of death in developing countries where changes in movement in the normal intestine are characterized by increased water content, volume, or frequency of bowel movements. This study aims to determine the antidiarrheal activity of honey and the combination of honey with guava leaf (Psidium guajava L.) infusion on mice. The method used is the protection method induced by Oleum Ricini. The results showed that honey 20 g / kgBB and a combination of honey 20g / kgBB with 30% Guava Leaf Infusion can provide antidiarrheal activity in mice.